Management of Borderline Resectable Pancreatic Adenocarcinoma - Jia, Yuxia; Wang, Tony JC; Allendorf, John; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
Pancreatic adenocarcinoma is the fourth most common cause of cancer-related death among U.S. men and women. Despite much effort in translational research, pancreatic adenocarcinoma remains a challenging disease with an overall 5-year survival rate less than 5%. To date, the only potentially curative treatment for managing pancreatic adenocarcinoma is surgical resection. However, more than 80% of patients are deemed either unresectable or metastatic upon diagnosis. For borderline resectable disease, although there is no high-level evidence supporting its use, an initial approach involving neoadjuvant therapy is preferred, as opposed to immediate surgery. In this year’s ASCO Gastrointestinal Cancers Symposium, several studies were presented with approaches towards treating borderline resectable pancreatic adenocarcinoma. Retrospective studies (Abstract #280, #304, #327) were presented and showed that neoadjuvant chemoradiation were associated with higher rates of negative margin resection and better survival. The tolerability of accelerated fraction radiotherapy with concomitant capecitabine was demonstrated in a phase I study (Abstract #329). More effective therapeutic approaches and prospective studies are needed for this devastating illness. This highlight article will focus on the management of borderline resectable pancreatic adenocarcinoma.